Anthropometric indicators as screening instrument for falls in the elderly - Drielly Soares Freitas; Juleimar Soares Coelho de Amorim; Renata Maciulis Dip; Marcos Aparecido Sarria Cabrera; Mara Solange Gomes Dellaroza; Celita Salmaso Trelha (Universidade Federal de Santa Catarina, 2016)
Anthropometric indicators enable professionals for predicting risk of falls in the elderly; however, there is a gap in literature on reference values. This study analyzes anthropometric indicators such as screening tests for falls in the elderly. Cross-sectional population-based systematic sampling was conducted through a household survey and body composition assessment. Anthropometric measurements were performed using portable electronic scale and stadiometer. Bioimpedance device was used to measure body mass index, body fat and lean body mass. Falls were evaluated in the 12 months preceding the interview as a dependent variable. Discriminatory analysis was performed for falls through the ROC curve, sensitivity, specificity, positive and negative predictive values. Overall, 275 older adults participated in this study, whose prevalence of falls was 23.6%. The average body mass index was 27.8kg/cm2 and 52.1% of individuals were overweight. Among older men, height (ROC=0.68; 95%CI 0.54-0.78) and lean body mass (ROC=0.63, 95%CI 0.58- 0.76) were associated to the occurrence of falls. When considering cutoff of 52.2kg and 166cm, sensitivity was obtained in 75% and high negative predictive values (88.1% and 89.1% respectively). For women, lean body mass (ROC=0.61, 95%CI 0.30-0.49) and body mass (ROC=0.60, 95%CI 0.53-0.72) were relevant from the optimal cutoff point of 28.9% and 57.2kg/m2. Lean body mass was more sensitive (63.2%) and body mass little more specific (64.3%), both with high negative predictive values (82.0% and 83.0%). The indicators used were able to discriminate older adults who have suffered from falls.